Impact of Aging and Cytomegalovirus on Immunological Response to Influenza Vaccination and Infection - Merani, Shahzma; Pawelec, Graham; Kuchel, George A.; McElhaney, Janet E. (Frontiers in Immunology, 2017)
The number of people over the age of 60 is expected to double by 2050 according to the WHO. This emphasizes the need to ensure optimized resilience to health stressors in late life. In older adults, influenza is one of the leading causes of catastrophic disability (defined as the loss of independence in daily living and self-care activities). Influenza vaccination is generally perceived to be less protective in older adults, with some studies suggesting that the humoural immune response to the vaccine is further impaired in cytomegalovirus (CMV)-seropositive older people. CMV is a β-herpes virus, infection which is generally asymptomatic in healthy individuals. The majority of older adults possess serum antibodies against the virus, indicating latent infection. Age-related changes in T-cell mediated immunity are augmented by CMV infection, and may be associated with more serious complications of influenza infection. This review focuses on the impact of aging and CMV on immune cell function, the response to influenza infection and vaccination, and how the current understanding of aging and CMV can be used to design a more effective influenza vaccine for older adults. It is anticipated that efforts in this field will address the public health need for improved protection against influenza in older adults, particularly with regard to the serious complications leading to loss of independence.